Building corporate reputation with stakeholders: exploring the role of message ambiguity for social marketers - Dickinson, Sonia; Beverland, M.; Lindgreen, A. (Emerald Group Publishing Limited, 2010)
Purpose – Managing the corporate reputation of hybrid firms (organizations that act commercially to pursue social agendas) involves particular challenges because of competing stakeholder interests. With reference to the Trappist beer market, the paper seeks to identify the value of message ambiguity in reducing stakeholder tension, while simultaneously achieving a clear market positioning. Design/methodology/approach – In total, 25 in‐depth interviews were conducted with brand marketers, owners, channel buyers, industry representatives and consumers. Findings – The findings demonstrate how ambiguous communications minimize tension between stakeholders. One form of ambiguous message strategy is identified – i.e. the deliberate use of “authenticity” as a positioning device. This positioning allows stakeholders to ascribe conflicting meanings to the Trappist brand, resulting in increased reputation and decreased stakeholder tension. Research limitations/implications – The use of authenticity and message ambiguity represents one means of balancing stakeholder interests, while achieving a clear market position. The paper believes the findings are particularly relevant for social marketers and managers of highly symbolic brands. Originality/value – Marketers can reduce stakeholder conflict through the use of brand images that emphasize normative as opposed to performance‐based commitments. Such commitments need to be broad enough to allow different stakeholders to ascribe their own meaning to the brand without diminishing the strength of the firm's market position.